PELAKSANAAN PEMUTUSAN HUBUNGAN KERJA TERHADAP PEKERJA YANG TERKENA PEMUTUSAN HUBUNGAN KERJA SEPIHAK KARENA KESALAHAN BERAT BERDASARKAN PUTUSAN MK NO. 012/PUU-I/2003 - Emilya Costa Yolanda R (Fakultas Hukum Universitas Tarumanagara, 2021)
This thesis discusses the implementation of termination of employment for workers who affected by unilateral termination of employment due to serious errors based on Constitutional Court Decision No. 012/PUU-I/2003 study of Medan District Court Decision Number:10/Pdt.Sus-Phi/2017/PN.Mdn. This study uses a normative legal research method with a prescriptive nature of research. From this study, two problems were taken, how the implementation of termination of employment for workers who were affected by unilateral termination of employment due to serious errors based on Constitutional Court Decision No. 012/PUU-I/2003; and what are the consideration of the Panel of Judges in makin decisions regarding termination of employment due to serious errors. That the implementation of termination of employment due to serious errors can be carried out after obtaining a criminal court decision that has legal force. Everyone who has been terminated due to serious misconduct is entitled to protection and certainty through a fair legal process.